The Radical Lives of Helen Keller. - Nielsen, Kim E. (History of disability series., 2004)
Several decades after her death in 1968, Helen Keller remains one of the most widely recognized women of the twentieth century. But the fascinating story of her vivid political life--particularly her interest in radicalism and anti-capitalist activism--has been largely overwhelmed by the sentimentalized story of her as a young deaf-blind girl. Keller had many lives indeed. Best known for her advocacy on behalf of the blind, she was also a member of the socialist party, an advocate of women's suffrage, a defender of the radical International Workers of the World, and a supporter of birth control--